Design and fabricate chair with flip table - Mohd Iqbal Anas, Mat Nawi (2007)
In design process, many element must be consider such as customer needs, ergonomic and many more. To design something that already have in market, the customer needs is very important element to consider. One of the things that regularly used by human to sit is chair. Nowadays, many design of chair have in market. The chair with flip table is thing that commonly use in university and collage. The problem with the design of chair with flip table that use now is the site of flip table and the size of the chair. As we know, the chair just have one flip table only whether on left site or on the right site. In university, the chair with right site of flip table is usually use. It can give a problem to student who used the left hand to write. On the other hand, the design of new chair of flip table must consider this problem. The design must comfortable to all user beside it can save space.